Kombinasi Metode SAW dan WASPAS Dalam Pemilihan Seleksi Penerimaan Tenaga Kerja Baru - Sohan Fafarihna; Dinda Afwani; Soeb Aripin (TIN: Terapan Informatika Nusantara, 2022)
The company can run and develop forward with the presence of employees or workers who are capable of according to the company's needs. CV Turbo Mandiri Perkasa is a company that requires many employees who are employed in various fields within the company. The process of accepting new workers with various criteria and the desired quality, Assessing the ability of prospective employees so that highly superior employees are obtained. For the determination of labor acceptance so far it is still done manually, the lack of a supporting system that causes the quality of employees to be accepted so far has been complied with. The assessment process carried out manually takes a long time and creates opportunities for fraud in the assessment process. To overcome this, a fast and computerized system is needed, which is able to facilitate the determination of the selection of new workers based on the criteria determined by CV. Turbo Mandiri mighty. In this study, researchers used two combined methods, namely the Simple Additive Weighting (SAW) method and the Weighted Aggregated Sum Product Assessment (WASPAS) method. These methods were chosen because the techniques used in them can determine the best weight value from several predetermined criteria. So that each attribute can be selected from the best alternative results. This study resulted in 1 prospective worker who was entitled to graduate as an employee, namely an applicant named Edianto Simanihuruk from Alternative A3.